Kenduri Nangal sebagai Tradisi Selamatan pada Suku Gayo Desa Leles Aceh Timur - Firdaus, Muhammad (SEURAYA Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract Indonesia, with its diverse ethnic groups and customs, is rich in various cultures. Traditions are ancestral legacies that continue to be preserved by Indonesian communities, with some traditions performed annually. The Gayo people, for example, maintain their cultural traditions due to their religious significance and their positive impact on the community. One such tradition is Kenduri Nangal. This study aims to describe and analyze the Kenduri Nangal tradition within the Gayo culture. The research employs a descriptive qualitative method, with data collected directly from the field. Data collection methods include direct observation and interviews. The research findings reveal the socio-cultural and religious conditions of the village of Leles, highlighting its unique characteristics. The Kenduri Nangal ritual involves cooking food from buffalo meat, with the community working together in the preparation. After cooking, the food is placed on plates lined with leaves, followed by a communal prayer led by a tengku. Keywords: Nangal, Gayo, East Aceh